Rate coefficients for h+ ions in n-Butanol gas - Nikitović Željka; Raspopović Zoran (Science of Sintering, 2022)
In this work we show predictions for the low energy cross sections and transport properties for the H+ ions in n-Butanol gas. These data are needed for modelling in numerous applications of technologically importance. Appropriate gas phase enthalpies of formation for the products were used to calculate scattering cross section as a function of kinetic energy. Calculated cross sections can be used to obtain rate coefficients as a function of E/N (E -electric field strength; N-gas density) for H+ in n-Butanol gas.